BETTY FREUND: A NURSE IN FRANCE - Part II - Hugo, Betty (Scientia Militaria - South African Journal of Military Studies, 2012)
Accounts of Betty's death and funeral service, newspaper cuttings, and a copy of the programme issued at a Memorial Service held in Cape Town in 1925